2021
DOI: 10.21776/ub.jam.2021.019.02.17
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Advantage to Mediate the Influence of Product Innovation and Entrepreneurial Orientation on Marketing Performance in Small and Medium Industry

Abstract: This study aims to analyze the effect of product innovation, entrepreneurial orientation, and competitive advantage on marketing performance; test the effect of product innovation and entrepreneurial orientation towards marketing performance through competitive advantage as a mediation variable. The sample in this study was 69 owners of small and medium industries bakery in Ponorogo Residence who had made innovations on their products. The sampling technique in this study uses total sampling. Data analysis tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The results of this research indicate that Competitive advantage has a correlation value of 0.380, which means that Competitive advantage has a positive and significant relationship to Marketing performance directly and contributes 38%. In line with the research of (Wulandari & Murniawaty, 2019), (Daengs GS et al, 2019), showed that Competitive advantage has a significant effect on marketing performance, same research from (Dahana et al, 2021), (Winarso et al, 2020), (Puspaningrum, 2020), (Harjadi et al, 2020), (Wahyu Yanuarti, 2019), (Amin et al, 2019), (Nofrizal et al, 2021), (Managing et al, 2018, (Sugiyarti, 2016), (Dewi Ni Made Putri & Ni Wayan Ekawati, 2017), (Arbawa & Wardoyo, 2018) (Hasniaty et al, 2019, Competitive advantage has a direct positive effect on marketing performance. Empirical findings (Markus et al, 2019), show that the differentiation strategy has a significant positive effect on competitive advantage; Innovation has a significant positive effect on company performance, but competitive advantage does not have a significant positive effect on company performance The implication of this research is that MSMEs actors must seriously seek competitive advantage for the products or services offered to consumers.…”
Section: A Direct Effect Of Competitive Advantage On Marketing Perfor...supporting
confidence: 74%
“…The results of this research indicate that Competitive advantage has a correlation value of 0.380, which means that Competitive advantage has a positive and significant relationship to Marketing performance directly and contributes 38%. In line with the research of (Wulandari & Murniawaty, 2019), (Daengs GS et al, 2019), showed that Competitive advantage has a significant effect on marketing performance, same research from (Dahana et al, 2021), (Winarso et al, 2020), (Puspaningrum, 2020), (Harjadi et al, 2020), (Wahyu Yanuarti, 2019), (Amin et al, 2019), (Nofrizal et al, 2021), (Managing et al, 2018, (Sugiyarti, 2016), (Dewi Ni Made Putri & Ni Wayan Ekawati, 2017), (Arbawa & Wardoyo, 2018) (Hasniaty et al, 2019, Competitive advantage has a direct positive effect on marketing performance. Empirical findings (Markus et al, 2019), show that the differentiation strategy has a significant positive effect on competitive advantage; Innovation has a significant positive effect on company performance, but competitive advantage does not have a significant positive effect on company performance The implication of this research is that MSMEs actors must seriously seek competitive advantage for the products or services offered to consumers.…”
Section: A Direct Effect Of Competitive Advantage On Marketing Perfor...supporting
confidence: 74%
“…In the competition between producers, companies that can increase the company achievements both in terms of total revenue and the number of customers indicate that the performance of the company has been going well. However, if marketing performance decreases, income and expenses will become unbalanced and will result in the bankruptcy of the company (Dahana et al, 2021). Apart from the intense competition amid this pandemic and the increasing scrutiny of customers, other possibilities that have caused a decline in marketing performance are companies that may be less adaptable to changing needs and trends, lack of market orientation, and lack of innovations in the products offered.…”
Section: Introductionmentioning
confidence: 99%
“…These studies do show variations in the structure of the research model, but the authors suspect that the structure of the research model that has been built has not been able to provide a comprehensive (holistic) picture and related to each other (integrated) dalam looking at marketing performance. Several relevant previous studies stated that market orientation and entrepreneurial orientation have a positive and significant effect on product innovation (Atuahene-Gima & Ko, 2001) (Atuahene-Gima & Ko in Dahana & Nur Khusniyah Indrawati Mugiono, 2021); Entrepreneurial orientation as a strategic effort to achieve competitive advantage (Covin & Miles in Cindera Fatikha, Mintarti Rahayu, 2021) and competitive advantage are factors that can mediate the influence of entrepreneurial orientation and pasar orientation on marketing performance.…”
Section: Introductionmentioning
confidence: 99%